Strategi Storytelling @menjadimanusia.id dalam mempromosikan kesadaran kesehatan mental bagi generasi Z - Tulle, Joyce Irene Grace; Devi Wening Astari (Jurnal Mahasiswa Komunikasi Cantrik, 2025)
Instagram has become one of the platforms for conveying information through engaging narratives, easily accessible, close to daily life, especially for Generation Z. This study aims to investigate the storytelling content of the Instagram account @menjadimanusia.id in fostering mental health awareness among Generation Z. This study uses a qualitative method. Data collection techniques included non-participatory observation of content in April 2025 and in-depth interviews with 10 Generation Z followers of the @menjadimanusia.id account for 2 years. The results of the study show that storytelling content in carousel format is the preferred format by Generation Z in building mental health awareness because it delivers messages gradually, concisely, and touchingly. Reels and reflective quote content strengthen the emotional resonance of Generation Z. This study also found that Generation Z follows the account @menjadimanusia.id because they feel emotionally connected to the presented narratives that reflect personal experiences, psychological pressures, or inner struggles, thereby providing positive energy that helps build their mental health awareness.